Safety and effectiveness of nurse telephone consultation in out of hours primary care: randomised controlled trial. Issue 7165 (17th October 1998) - Lattimer, Val; George, Steve; Thompson, Felicity; Thomas, Eileen; Mullee, Mark; Turnbull, Joanne; Smith, Helen; Moore, Michael; Bond, Hugh; Glasper, Alan
Abstract: Objective To determine the safety and effectiveness of nurse telephone consultation in out of hours primary care by investigating adverse events and the management of calls. Design Block randomised controlled trial over a year of 156 matched pairs of days and weekends in 26 blocks. One of each matched pair was randomised to receive the intervention. Setting One 55 member general practice cooperative serving 97 000 registered patients in Wiltshire. Subjects All patients contacting the out of hours service or about whom contact was made during specified times over the trial year. Intervention A nurse telephone consultation service integrated within a general practice cooperative. The out of hours period was 615 pm to 1115 pm from Monday to Friday, 1100 am to 1115 pm on Saturday, and 800 am to 1115 pm on Sunday. Experienced and specially trained nurses received, assessed, and managed calls from patients or their carers. Management options included telephone advice; referral to the general practitioner on duty (for telephone advice, an appointment at a primary care centre, or a home visit); referral to the emergency service or advice to attend accident and emergency. Calls were managed with the help of decision support software. Main outcome measures Deaths within seven days of a contact with the out of hours service; emergency hospital admissions within 24 hours and within three days of contact; attendance at accident and emergency within three days of a contact; number and management of calls in each arm of the trial. Results 14 492 calls were received during the specified times in the trial year (7308 in the control arm and 7184 in the intervention arm) concerning 10 134 patients (10.4% of the registered population). There were no substantial differences in the age and sex of patients in the intervention and control groups, though male patients were underrepresented overall. Reasons for calling the service were consistent with previous studies. Nurses managed 49.8% of calls during intervention periods without referral to a general practitioner. A 69% reduction in telephone advice from a general practitioner, together with a 38% reduction in patient attendance at primary care centres and a 23% reduction in home visits was observed during intervention periods. Statistical equivalence was observed in the number of deaths within seven days, in the number of emergency hospital admissions, and in the number of attendances at accident and emergency departments. Conclusions Nurse telephone consultation produced substantial changes in call management, reducing overall workload of general practitioners by 50% while allowing callers faster access to health information and advice. It was not associated with an increase in the number of adverse events. This model of out of hours primary care is safe and effective.